The Influence of Student Organizations on the Civic Disposition of Riau University Students - Fakhri Jannata Sholihin; Hambali Hambali; Indra Primahardani (CV. Rayyan Dwi Bharata, 2024)
This research is motivated by students' lack of optimal application of civic disposition. Therefore, students' weak application of civic disposition is partly influenced by students becoming members of student organizations. The purpose of this research is to find out whether there is an influence of student organizations on the civic disposition of students at the Universitas Riau. The population in this research was Universitas Riau students, totaling 30,292 people. Determining the sample in this research used the Isaac Michael table using an error level of 10%, thus obtaining 268 samples. The data collection method used in this research was a questionnaire. Based on the results of descriptive analysis research, it showed that the condition of student organizations was included in the good category with a percentage of 60% and the condition of civic disposition is included in the very good category with a percentage of 89%. Based on data analysis in this research, it was found that there was a positive and significant influence between student organizations on civic disposition, which showed that the value was fcount 84.525 ≥ ftable 3.88 and a significant value of 0.000 ≤ 0.05. Thus, it can be concluded that Ho is rejected and Ha is accepted, so simultaneously student organizations (X) have a significant influence on the civic disposition (Y) of Universitas Riau students. The results of the analysis of the coefficient of determination test or contribution of the influence of student organizations (X) on civic disposition (Y) were 31%, while 69% was influenced by other variables not examined in this research.